Peran Produktif Wakaf pada Bank Wakaf Mikro di Masyarakat Kota Jambi - Anggraeni, Lidya; Anggraini, Dessy (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the significant role of productive waqf fund benefits distributed by micro waqf banks to SMEs, with the goal of improving well-being, and to assess the impact of productive waqf funds in micro waqf banks in developing the businesses of SMEs. Using a qualitative approach and descriptive research methods, the researcher collected data from various sources, including in-depth interviews with relevant parties such as the Micro Waqf Bank Management and recipients of productive waqf funds in the hope of explaining the facts and conditions needed for the research. The informants in this study consisted of 20 individuals who met the criteria of understanding and being able to argue when the researcher explored and delved into questions and statements, as well as individuals who received and used productive waqf funds, thus experiencing the impact and benefits of these funds for the sustainability of their businesses and the improvement of their quality of life. The research results indicate that the role of Micro Waqf Banks for SMEs and the impact of productive waqf fund assistance are significant. These banks play a crucial role in supporting the growth and development of SMEs. Micro Waqf Banks provide access to capital for SMEs who often face difficulties in obtaining loans from other financial institutions, thus helping them expand their businesses, create job opportunities, and enhance economic well-being. The bank's role also includes community economic empowerment through training and mentoring. The impact of productive waqf fund assistance on the development of SMEs' businesses is also highly significant. This assistance helps SMEs in business development, improving competitiveness, and overcoming capital constraints. In addition to the economic impact, productive waqf fund assistance also builds self-confidence, motivation, and the overall quality of life for SMEs.